GIS-integrated multi-criteria suitability analysis for healthcare facilities site selection in Rajouri district, Jammu and Kashmir, India - Ahmed, Arshad; Kheraj,; Ali, Amjed; Rani, Kiran; Meenaxy, (Acta Geographica Debrecina Landscape & Environment series, 2023)
The study aims to develop a Decision Support model for the selection of a suitable site to establish a new healthcare center with adequate facilities based on the analytical hierarchy process (AHP) in the Rajouri district of Jammu and Kashmir. This study utilized AHP and GIS to identify an appropriate location for a new healthcare center. The study employed eight criteria to evaluate potential locations and utilized pairwise comparison to assign weights to each criterion. GIS-based spatial analysis was used to create factor and suitability maps for each criterion. Suitability was evaluated on a scale of 0 to 10 and each factor map was combined using the ArcGIS weighted overlay selection tool. The final map of the study represents the suitable site for a healthcare center in the Rajouri district and it shows the sites from the highly suitable to the least suitable area. In Rajouri district, mostly the central part can be considered very suitable as the population density of this area is higher compared to other areas of the district. The southwestern parts of the district are moderately suitable or least suitable sites for a new healthcare center. The study displays the pattern of the existing location of healthcare centers, mostly, the existing locations are not proper and suitable. Therefore, in the future, the allocation of healthcare centers must be in more adequate areas. Policymakers and healthcare professionals can be benefitted from this study in selecting suitable locations for future hospitals, which could ultimately improve access to healthcare services in the region. Additionally, the study can be contemplated in developing new policies for better transportation system in the study area.